Recent Applications in Sol-Gel Synthesis - Chandra, Usha (IntechOpen, 2017)
Versatility, extended compositional ranges, better homogeneity, lesser energy consumption, and requirement of nonexpensive equipments have boosted the use of sol-gel process on top of the popularity in the synthesis of nanosystems. The sol-gel technique has not only revolutionized oxide ceramics industry and/or material science but has also extended widely into multidimensional applications. The book Recent Applications in Sol-Gel Synthesis comprises 14 chapters that deal mainly with the application-oriented aspects of the technique. Sol-gel prepared metal oxide (MO) nanostructures like nanospheres, nanorods, nanoflakes, nanotubes, and nanoribbons have been employed in biomedical applications involving drug deliveries, mimicking of natural bone, and antimicrobial activities. The possibility of controlling grain size in aerogel and preparation of ultrahigh-temperature ceramic (UHTC)-based materials, fluorescent glasses, ultraviolet photosensors, and photocatalysts have been discussed in detail by the experts in the field. The usefulness of sol-gel materials as active GRIN, as textile finisher, and as leather modifier with water-repellent and oil-resistive properties would be an incentive for researchers keen to pursue the field.